2018
DOI: 10.1016/j.neubiorev.2017.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal selective serotonin reuptake inhibitor medication (SSRI) effects on social behaviors, neurodevelopment and the epigenome

Abstract: Recent research has linked early life exposure to selective serotonin reuptake inhibitor medications (SSRIs) to modifications of social behaviors in children. Serotonin is a key regulator of neurodevelopment, social behaviors and mental health, and with the growing use of SSRIs to treat maternal affective disorders during the perinatal period, questions have been raised about the benefits and risks of perinatal SSRI exposure on the developing child. This review will highlight how perinatal SSRIs affect materna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 210 publications
4
59
1
Order By: Relevance
“…Epidemiological studies have demonstrated that optimizing brain development in early life has been associated with long-term consequences for individuals, for instance, academic performance, the level of education attained [1][2][3], and mental well-being in adulthood [4]. In particular, early-life environmental factors such as smoking, healthy lifestyle, and other factors have been suggested to play a major role in neurodevelopmental processes [5][6][7][8][9][10][11]. Accordingly, some previous studies have evidenced a relationship between suboptimal maternal diet in pregnancy and poorer mental and psychomotor development in offspring [5,6,[12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have demonstrated that optimizing brain development in early life has been associated with long-term consequences for individuals, for instance, academic performance, the level of education attained [1][2][3], and mental well-being in adulthood [4]. In particular, early-life environmental factors such as smoking, healthy lifestyle, and other factors have been suggested to play a major role in neurodevelopmental processes [5][6][7][8][9][10][11]. Accordingly, some previous studies have evidenced a relationship between suboptimal maternal diet in pregnancy and poorer mental and psychomotor development in offspring [5,6,[12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Data were analyzed using the software Statistica (Dell Inc.). Due to previous findings of sexually differentiated patterns of outcomes in the response to pSSRIs and maternal stress exposure on behavioral measures, HPA axis, hippocampal plasticity, and additional neurobehavioral outcomes (Gemmel et al, 2018a;Gobinath et al, 2016;Rayen et al, 2015), factorial ANOVAs were conducted separately for each sex on behavioral measures, corticosterone, CBG, as well as on measures of hippocampal plasticity and GR density with condition (pre-gestational stress/control) and treatment (fluoxetine/vehicle) as independent factors. Factorial ANOVAs with condition (pre-gestational stress/control), treatment (fluoxetine/vehicle), and sex (male/female) as independent factors can be found in…”
Section: Discussionmentioning
confidence: 99%
“…Selective Serotonin Reuptake Inhibitor medications (SSRIs) are commonly prescribed during pregnancy to treat maternal stress-related mood disorders (Gemmel et al, 2018a;Oberlander et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depression is a stress-related, affective disorder, with prevalence of 10-18% among pregnant women all over the world. Exposure to prenatal stress represents a great risk factor for developing pregnancy diseases (preeclampsia, miscarriages, gestational hypertension and hypoxia of the fetus), altered fetal development, low birth weight and a range of neurobehavioral disturbances of a child, including autism, anxiety and depression (St-Pierre et al, 2016; Kiryanova et al, 2017;Gemmel et al, 2018). During gestation, 2-3% women are treated with antidepressants (AD), mostly with selective serotonin reuptake inhibitors (SSRI) or selective serotonin and norepinephrine reuptake inhibitors (SNRI).…”
mentioning
confidence: 99%